PEMBELAJARAN ERA DISRUPTIF MENUJU MASYARAKAT 5. 0 - Aman, Muhammad; Fitria2, Happy (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— At present we have entered the fourth generation industrial era. The hallmark of this generation's revolution is the amount of human power that has been replaced by robots that have been controlled by computers. The education world certainly has its own challenges in responding to this change. Therefore, reformulation of the learning process is needed both at school and outside of school. Utilization of technology certainly can not be avoided because it is already in its time. The teacher is always required to update about these changes in order to be able to prepare students to face these changes. One important thing is that HOTS-based learning has become a necessity so that students are accustomed to thinking critically so that they can develop their creativity. Learning is an important tool in growing HOTS thinking. Learning generally leads to higher-order thinking processes. During the learning process the teacher should design a process that is able to foster high creativity. Therefore teachers and students must understand the characteristics of learning correctly. Keywords— Disruptive Era Learning Abstrak—Saat ini kita telah memasuki era industri generasi ke empat. Ciri khas revolusi generasi ini adalah banyaknya tenaga manusia yang sudah digantikan oleh robot yang telah dikendalikan oleh komputer. Dunia pendidikan tentunya mempunyai tantangan tersendiri dalam menyikapi perubahan ini. Oleh karena itu, diperlukan reformulasi proses pembelajaran baik di sekolah maupun di luar sekolah. Pemanfaatan teknologi tentunya tidak bisa dihindari karena memang sudah zamannya. Guru senantiasa dituntut untuk update tentang perubahan ini agar mampu menyiapkan siswa menghadapi perubahan ini. Salah satu hal penting adalah pembelajaran berbasis HOTS sudah menjadi keharusan agar siswa terbiasa berpikir kritis sehingga mampu mengembangkan kreatifitasnya. Pembelajaran merupakan sarana penting dalam menumbuhkan berpikir yang HOTS. Belajar secara umum mengarah kepada proses berpikir tingkat tinggi. Selama proses pembelajaran guru seyogyanya merancang proses yang mampu menumbuhkan kreatifitas yang tinggi. Oleh karena itu guru dan siswa harus paham karakteristik pembelajaran secara benar. Kata Kunci— Pembelajaran Era Disruptif